CHARACTERISTICS OF LOCAL GOVERNMENTS ON COMPLIANCE WITH DISCLOSURE OF ANNUAL FINANCIAL STATEMENTS - Dian Andriani (Jurnal Ekonomi, 2022)
Based on Government Regulation no. 71 of 2010 concerning SAP, the general purpose of financial statements is to present information about the financial position, budget realization, cash flow, and financial performance of a reporting entity that is useful for users in making and evaluating decisions regarding resource allocation. The purpose of this study is to determine the characteristics of local governments on compliance with financial statement disclosures, using descriptive analysis as a research method, and involving a qualitative approach strategy, the results of this study explain that, Public accountability is a principle that ensures that every government administration activity can be accounted for. openly and fairly by the actors to the parties affected by the implementation of the policy, including the community itself, especially the realization of transparency and accountability of state/regional finances in the form of government financial reports. There are several research variables that have a significant influence on the quality of financial reports, such as the characteristics of local governments, the level of dependence, regional expenditures, and audit opinions on the quality of financial reporting. Thus, in terms of financial governance of a region, opinion is a means for the community to assess whether the financial management in their area has been managed properly or not. The BPK audit opinion can give public confidence in the local government if the opinion is good, but if the opinion on the financial statements received by the region is bad, the public will also doubt financial management in the region